New report of the rare Sciadonus alphacrucis Melo et al., 2022 (Teleostei, Ophidiiformes, Bythitidae), DNA barcoding, and range extension in the western South Atlantic - dos Reis Júnior, Marcos Roberto; Caixeta, Heloisa De Cia; Oliveira, Claudio [UNESP]; Melo, Marcelo Roberto Souto de (Wiley, 2024)
Sciadonus alphacrucis Melo, Gomes, Møller & Nielsen, 2022 is a rare deep-sea species, previously known from only two specimens collected off São Paulo State, southeastern Brazil, in the western South Atlantic. Herein, we report a new specimen of S. alphacrucis collected on the continental slope off Santa Catarina State, southern Brazil, thereby extending its known distribution by 420 km. Additionally, we provide the new meristic and morphometric data, the molecular identification using sequences of the cytochrome c oxidase subunit I (COI), an updated distribution map, and a discussion of troglomorphic traits.
Keywords: Cuskeels; cytochrome c oxidase subunit I; deep sea; new record; R.V. Alpha Crucis